Interleukin-6 Expression of Osteogenic Cell Lines Grown on Laser-Treated and Hydroxyapatite-Coated Titanium Discs - Santos, Ana Flávia Piquera [UNESP]; Cervantes, Lara Cristina Cunha [UNESP]; Okamoto, Roberta [UNESP]; Guastaldi, Antonio Carlos [UNESP]; Queiroz, Thallita Pereira; Panahipour, Layla; Gruber, Reinhard; Souza, Francisley Ávila [UNESP] (MDPI, 2023)
The laser treatment and hydroxyapatite coating of dental implants are supposed to enhance osseointegration, but prior to preclinical testing, any negative impact on cell viability should be ruled out. This study aimed to evaluate the response of murine osteogenic cell lineage MC3T3-E1 and the bone marrow-derived stromal cells ST2 to surface modifications of machined titanium discs, e.g., laser treatment without and with hydroxyapatite coating, as well as sandblasting followed by acid etching. Scanning electron microscopy and the contact angle measurements revealed that laser treatment caused a honeycomb surface and higher wettability compared to a machined or sandblasting acid-etched surface. Hydroxyapatite coating, however, not only reduced the viability of MC3T3-E1 and ST2 cells but also provoked the expression and release of interleukin-6. These findings suggest that the laser treatment of titanium supports its hydrophilicity, but adding hydroxyapatite can reduce cell viability and induce the concomitant release of inflammatory cytokines.
Keywords: biocompatible materials; cell culture techniques; hydroxyapatite; inflammation mediators; scanning electron microscopy; titanium discs